Effect of erythritol on verrucous dermatitis in dairy cattle - Sasaki, N.(Obihiro Univ. of Agriculture and Veterinary Medicine, Hokkaido (Japan)); Takakuwa, J; Nishii, S; Ishii, M; Kadohira, M; Naitou, Y; Manabe, H; Yamada, H (Journal of the Japan Veterinary Medical Association, 2009)
The efficacy of the local application of erythritol and conventional antibiotic therapy was compared in bovine verrucous dermatitis. In February 2008, 15 hooves of ten Holstein dairy cows with verrucous dermatitis were examined physically at tie stall farms in the Tokachi area, Hokkaido, Japan. Lesion scores, lesion sizes, affected areas, and tenderness scores of the hooves were assessed. Subjects received erythritol (Group E, n = 8) or oxytetracycline (Group O, n = 7). The lesions were examined before and two, five, and 12 days after treatment. Use of erythritol led to a significant improvement in lesion scores and tenderness scores, and the effectiveness of both treatments were similar. Erythritol was considered effective in bovine verrucous dermatitis.